Micro-electric tractors for deep bed farming and sustainable micro-grid electricity - Williams, Toby; Wilson, Jonathan; Partington, Lee; Andrews, Cameron; Chavula, Isaac; Gondwe, France; Betts, Tom; Strickland, Dani (Frontiers in Energy Research, 2024)
This paper describes an innovative method to provide a micro-electric tractor which has been developed as part of an initiative that aims to provide socially inclusive and affordable green energy solutions to smallholders in sub-Saharan Africa. It utilizes a 15.0kW solar array and battery system to power micro electric tractors for an agricultural practice in Malawi called Deep Bed Farming. Deep Bed Farming has been claimed to increase smallholder crop yield by about two and half times which increases revenue by up to 12 times. The extra revenue can then be used to perpetually purchase domestic energy from the solar array, creating a self-sustaining model for decentralized energy access. However, the requirement for land preparation is onerous and mechanization is needed to help overcome barriers to entry. This paper describes the technical requirements of a solar base station and micro tractor for use with Deep Bed Farming technique. The paper covers the design of 5.9kWp modular solar design and a 10.0kWh rated micro tractor. Testing was undertaken as an isolated grid in Loughborough as a precursor to plans for large scale testing in Malawi.